2023
DOI: 10.1007/s42765-023-00299-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanocomposite Fibrous Membranes for Sustainable Face Mask Based on Triboelectric Nanogenerator with High Air Filtration Efficiency

Abstract: Air pollution caused by the rapid development of industry has always been a great issue to the environment and human being’s health. However, the efficient and persistent filtration to PM 0.3 remains a great challenge. Herein, a self-powered filter with micro–nano composite structure composed of polybutanediol succinate (PBS) nanofiber membrane and polyacrylonitrile (PAN) nanofiber/polystyrene (PS) microfiber hybrid mats was prepared by electrospinning. The balance between pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To interpret the PM filtration mechanisms, SEM observations were conducted for the PLA membranes after filtration tests (Figure m–p). It could be clearly observed that the microsized PMs were firmly adhered to the fiber nodes of OSC-PLA NFMs through physical interception, while the nanosized PMs were tightly captured by the fibers (Figure n–p). , Moreover, the excellent hydrophobic feature is a crucial prerequisite for ensuring the durability of the filter in a humid environment. , As illustrated in Figure S8, the contact angles of OSC-PLA NFMs were about 126.8°, indicating the potentially high humidity resistance …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To interpret the PM filtration mechanisms, SEM observations were conducted for the PLA membranes after filtration tests (Figure m–p). It could be clearly observed that the microsized PMs were firmly adhered to the fiber nodes of OSC-PLA NFMs through physical interception, while the nanosized PMs were tightly captured by the fibers (Figure n–p). , Moreover, the excellent hydrophobic feature is a crucial prerequisite for ensuring the durability of the filter in a humid environment. , As illustrated in Figure S8, the contact angles of OSC-PLA NFMs were about 126.8°, indicating the potentially high humidity resistance …”
Section: Resultsmentioning
confidence: 98%
“…49,50 As illustrated in Figure S8, the contact angles of OSC-PLA NFMs were about 126.8°, indicating the potentially high humidity resistance. 51 Performance Evaluation of TENG Air Filters. The excellent electroactivity means that OSC-PLA NFMs confer superior triboelectric properties.…”
Section: Figures 1c−f and S1mentioning
confidence: 99%
“…223 However, this type of mask exhibits poor stability in humid environments. To address this issue, Yang et al 224 developed a straightforward, self-powered air filtration face mask based on TENGs. The mask incorporates high filtration efficiency and long-term stable charges with polyacrylonitrile (PAN) nanofiber/polystyrene (PS) microfiber.…”
Section: Application Of F-tengsmentioning
confidence: 99%
“…Unlike electrets, which need to be recharged, and conductive materials, which require an external power source, triboelectric materials can use friction between materials of different electronegativity to generate electrical charge. Under mechanical deformation generated by facial expressions, breathing, or speaking, triboelectric face masks can be easily charged to achieve charge regeneration. A range of triboelectric materials have been developed to avoid degradation of the filtration performance due to charge dissipation and to prolong the practical use of masks (Table ).…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%